WED 241 Clinical relevance of regular blood monitoring in IG treatment. Issue 10 (13th September 2018) - Khalil, A; Compton, L; Kapoor, M; Groves, J; Nihoyannopoulos, L; Gosal, D; Rossor, A; Reilly, MM; Carr, AS; Lavin, T
Abstract : Background: ABN immunoglobulin (Ig) guidelines advise routine FBC and U and E monitoring with every treatment episode and screening for IgA deficiency. Aims: We audited compliance in inflammatory neuropathy patients on longterm treatment in two UK Neurology departments. We looked for evidence of clinically relevant haematological or AKI Ig-related events. Methods: Data was collected from Nov 2015 to Nov 2017. Accepted definitions for clinically and/or biochemically significant haemolysis, neutropenia, thrombocytopenia and AKI were used. Results: 1919 treatment episodes in 90 patients were analysed. Mean age (SD)=57.6 (14.4)years, 69.1% male, 74% CIDP (26% MMN), 94% IVIg (6% SCIg). Mean dose=1.57 (0.74) g/kg/month or 97.1 (37.3) g/infusion. No clinically significant episodes of haemolysis, neutropenia, thrombocytopenia or AKI occurred in relation to Ig treatment. An asymptomatic drop of >10 g/L Hb occurred in 68/1919 episodes in 38 individuals (3.5%); mean reduction 17.7 g/L, lowest Hb 99 g/L. Two patients with CRF (stage 3) received 28 (IV) and 104 (SC) infusions respectively without impact on eGFR. Two individuals with relative IgA deficiency (0.38 g/L, 0.4 g/L) received 16 infusions over 1.5 years without complications. Conclusions: No clinically significant Ig-related events were identified in this representative cohort. We suggest annual screening or clinically indicated testing as safe and more appropriate in longterm IVIg use.